Labor Share in National Income: Implications in the Baltic Countries - Aušra Razgūnė; Romas Lazutka (Review of Economic Perspectives, 2017)
Despite the fact that stability of labor share in national income is a key foundation in macroeconomic models, scientists acknowledge, that in the last three decades it has been declining around the world. The Baltic countries are not an exception; they follow similar patters to large economies, thus the research aims at determining economic factors at play. With the help of error correction model and time series data covering the past twenty years, we determine factors which contribute to the decline of labor share in the Baltic countries. We find significant long-term relationships between labor share and government spending, trade openness, and emigration. Government spending exhibits the highest contribution to variance of labor share in Lithuania, which also explains a large part of Latvia's labor share variations. We find many similarities between the analyzed countries, however some differences are also visible.
Keywords: J01; J30; E25; D33; 330; Baltic countries; income distribution; labor economics; labor share